ОЦІНЮВАННЯ ТА ЗМЕНШЕННЯ В РЕЖИМІ РЕАЛЬНОГО ЧАСУ НЕБЕЗПЕКИ КОЛИВНОГО ПОРУШЕННЯ СТІЙКОСТІ ОБ’ЄДНАНОЇ ЕНЕРГОСИСТЕМИ - Буткевич, О.Ф.; Чижевський, В.В. (Інститут електродинаміки НАН України, Київ, 2015)
An approach to damping problem solution of inter-area oscillations (IAO) in an interconnected power system (IPS) with use of an integrated damping system (IDS) is proposed. The tools of identifying of dominant modes of IAO are the information source for IDS. These tools in real-time analyse the IPS operational condition parameters and evaluate current risk of oscillatory loss of IPS stability. Some methods of signal analysis from the point of view of appropriateness of their use in IDS were examined. References 8, tables 2, figures 2.